Optimizing The Selection Of Best Employees Using The Saw Method - Wijaya, Jonathan; Eka Lia Febrianti; Winston, Frenky; Netrysa, Iza; Fernando, Felix (Jurnal Sains Informatika Terapan, 2024)
In the competitive culinary industry, particularly within the café sector, maintaining high service quality and operational efficiency is essential for business sustainability. Employee performance significantly influences both productivity and customer satisfaction, making an effective performance assessment system vital for fostering motivation and consistency among staff. This study implements a Decision Support System (DSS) based on the Simple Additive Weighting (SAW) method to evaluate employees across key criteria, such as attendance, daily performance, attitude, and teamwork. By applying the SAW method, the DSS enables a straightforward, objective, and data-driven approach to identifying top-performing employees, thus assisting management in recognizing outstanding contributions and boosting overall team motivation. The goal of this research is to ensure that the system can be easily implemented in the café environment and has a substantial impact on improving both employee performance and morale, contributing to enhanced service quality and operational success.